2008
DOI: 10.1016/j.cell.2008.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Pheromone-Sensitive Neurons Is Mediated by Conformational Activation of Pheromone-Binding Protein

Abstract: Detection of volatile odorants by olfactory neurons is thought to result from direct activation of seven-transmembrane odorant receptors by odor molecules. Here, we show that detection of the Drosophila pheromone, 11-cis vaccenyl acetate (cVA), is instead mediated by pheromone-induced conformational shifts in the extracellular pheromone-binding protein, LUSH. We show that LUSH undergoes a pheromone-specific conformational change that triggers the firing of pheromone-sensitive neurons. Amino acid substitutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
465
7
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 399 publications
(488 citation statements)
references
References 61 publications
(90 reference statements)
12
465
7
4
Order By: Relevance
“…The effect of indole on the structure of OBP4 correlates well with our previous findings for the Drosophila OBP LUSH, where binding of ligand induces a significant conformational ordering that is required to regulate its interactions with other components of the olfactory signaling cascade including sensory neuron membrane protein (26,53,57,58). Conformational heterogeneity has been observed in several other OBPs (14,17,59,60) and is most often associated with residues that regulate access to the ligand binding pocket.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The effect of indole on the structure of OBP4 correlates well with our previous findings for the Drosophila OBP LUSH, where binding of ligand induces a significant conformational ordering that is required to regulate its interactions with other components of the olfactory signaling cascade including sensory neuron membrane protein (26,53,57,58). Conformational heterogeneity has been observed in several other OBPs (14,17,59,60) and is most often associated with residues that regulate access to the ligand binding pocket.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, we and others have proposed that in some cases a specific complex between the OBP and odorant is required for odorant receptor activation (20 -25). In support of this, we demonstrated that a key amino acid substitution in a critical loop of the Drosophila melanogaster OBP LUSH could activate pheromone receptors in the complete absence of pheromone (23,26,27), providing direct evidence that the OBP is the ligand for the receptor complex. These differences in function most likely reflect the level of control, with responses to general odorants being less tightly regulated than other sexual or species-specific responses.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Here, the pheromone binds to carrier proteins that help transport the pheromone to olfactory receptors (ORs) located in the ORN membrane (Laughlin et al 2008;Vogt and Riddiford 1981). The candidate carrier protein in the drone antenna is ASP1 which contains a hydrophobic domain that is able to bind the apolar components of 9ODA (Pesenti et al 2008).…”
Section: Amor11 Is the Olfactory Receptor That Detects 9odamentioning
confidence: 99%